Blockchain For Education Purpose: Essential Topology - Aini, Qurotul; Lutfiani, Ninda; Santoso, Nuke Puji Lestari; Sulistiawati, Sulistiawati; Astriyani, Erna (APTISI Transactions on Management (ATM), 2021)
Blockchain technology is known for its large-scale digitisation trends that play an important role in various organisations. Because it is distributed and decentralized from blockchain, this feature makes the role of blockchain technologies based on products and services significantly different from previous technology offerings. The value proposition offered by this blockchain is very suitable to be applied in education. After a few years this caused disruption from various industry circles, current educational areas including those that are very perceived by the Indonesian people there is no progress and road in place. It is possible that in the next ten years, the educational actors who are less sensitive will one by one fall because of the storm-cast disruption technology. The educational institution is one of which is aware of the advantages and extraordinary potential of blockchain technology. Among other things, a digital signature certificate is important in the context of digital archiving to verify the authenticity of a document in an educational institution. But the lack of education from the community makes ignorance about the point of the advantage of blockchain technology that can be applied in the field of education. Therefore, a public understanding of the blockchain is packaged in the form of ontology on the education shutter. This research in particular is exploring the ontology approach of using root merkle methods in providing solutions to the application of blockchain, including slow process and small storage space. This issue causes it to be very difficult for educational institutions to store processes and stages of learning into the blockchain. This research can be the cornerstone of identifying solutions from certificates of digital signatures in terms of archiving, authentication and digital verification on the design of a new breakthrough framework with an ontology approach to blockchain educational design.